BENTURAN NILAI GENERASI Z DAN GURU: TENTANG PERGESERAN AKHLAK DALAM INTERAKSI KELAS DI KELAS IX MADRASAH TSANAWIYAH AL-MUNAWWARAH KOTA JAMBI - Tunnajah, Safina; Saputra, Edi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the clash of values ​​between Generation Z students and teachers and its implications for moral shifts in classroom interactions at MTs Al-Munawwarah, Jambi City. Using a qualitative approach with ethnographic methods, this study involved the principal, Akidah Akhlak teachers, and ninth-grade students as research subjects. Data collection was conducted through participant observation, in-depth interviews, and documentation. The results showed that value clashes occurred in four main forms: differences in communication and attitude expression, differences in the meaning of politeness and etiquette, tensions in classroom discipline and management, and the influence of digital culture and the social environment. Teachers interpreted changes in student behavior as a moral shift characterized by a weakening of sensitivity to interaction ethics, a decrease in the ability to position oneself, and a shift in standards of politeness from formal-hierarchical to casual-egalitarian. In responding to value clashes, teachers developed persuasive and communicative approaches, implemented reward and punishment systems, responded firmly to maintain order, and instilled values ​​through role models and habits. This research contributes to understanding the dynamics of character education in the digital era and offers recommendations for developing educational policies that are adaptive to the characteristics of Generation Z.